Functionalized Boron Nitride Nanosheets/Graphene Interlayer for Fast and Long‐Life Lithium–Sulfur Batteries. Issue 13 (25th January 2017) - Fan, Ye; Yang, Zhi; Hua, Wuxing; Liu, Dan; Tao, Tao; Rahman, Md Mokhlesur; Lei, Weiwei; Huang, Shaoming; Chen, Ying
Abstract : Lithium–sulfur (Li–S) batteries have a much higher energy density than Li ion batteries and thus are considered as next generation batteries for electric vehicle applications. However, the problem of rapid capacity fading due to the shuttling of soluble polysulfides between electrodes remains the main obstacle for practical applications. Here, a thin and selective interlayer structure has been designed and produced to decrease the charge transfer resistance and mitigate the shuttling problem, simply by coating the surface of cathode with a thin film of functionalized boron nitride nanosheets/graphene. Due to this thin and ultralight interlayer, the specific capacity and cycling stability of the Li–S batteries with a cathode of sulfur‐containing porous carbon nanotubes (≈60 wt% sulfur content) have been improved significantly with a life of over 1000 cycles, an initial specific capacity of 1100 mA h g −1 at 3 C, and a cycle decay as low as 0.0037% per cycle. This new interlayer provides a promising approach to significantly enhance the performance of Li–S batteries. Abstract : An ion‐selective interlayer of graphene and boron nitride nanosheet is designed and inserted between separator and cathode to decrease the charge transfer resistance, mitigate the shuttling problem, and enhance the performance of lithium–sulfur batteries. The hybrid interlayer is also expected to provide a new approach in other energy‐storage systems that require a barrier to control the ion transportations.